2021
DOI: 10.3390/jpm11121363
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Tumor Location on Long-Term Oncological Outcomes in Patients with Upper Tract Urothelial Carcinoma Treated with Radical Nephroureterectomy: A Systematic Review and Meta-Analysis

Abstract: Background: Upper tract urothelial carcinoma (UTUC) accounts for up to 10% of all urothelial neoplasms. Currently, various tumor-related factors are proposed to be of importance in UTUC prognostic models; however, the association of the primary UTUC location with oncological outcomes remains controversial. Thus, we sought to perform a systematic review and meta-analysis of the latest available evidence and assess the impact of primary tumor location on long-term oncological outcomes in patients with UTUC under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ureteral location is considered as an important negative prognostic factor in patients with UTUC. Recent meta-analysis including 10,537 patients with RPT and 6299 patients with UT demonstrated that ureteral location of UTUC is associated with decreased CSS, OS, and DFS [ 19 ]. More aggressive behavior of UT, potentially related to tumor’s surrounding environment (e.g., thin periureteral layer of muscular and fatty tissue, compared to renal parenchyma), raises the question about the safe delay interval in radical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral location is considered as an important negative prognostic factor in patients with UTUC. Recent meta-analysis including 10,537 patients with RPT and 6299 patients with UT demonstrated that ureteral location of UTUC is associated with decreased CSS, OS, and DFS [ 19 ]. More aggressive behavior of UT, potentially related to tumor’s surrounding environment (e.g., thin periureteral layer of muscular and fatty tissue, compared to renal parenchyma), raises the question about the safe delay interval in radical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in risk based on primary tumor location was found in a meta-analysis by Krajewski et al of over 16,000 patients ( 85 ). Patients with ureteral tumors were found to have significantly worse cancer-specific survival, overall survival, and disease-free survival than patients with renal pelvic tumors ( 85 ). Another meta-analysis by Wu et al reported similar findings, except for patients with pT3/4 and pN+ tumors ( 86 ).…”
Section: Factors Associated With Oncologic Outcomesmentioning
confidence: 96%